Social Media by Proxy: how older adults work within their ‘social networks’ to engage with social media - Gemma Webster; Frances Ryan (Information Research: An International Electronic Journal)
Introduction. This paper reports an exploratory qualitative study investigating the ways in which older adults are supported by social media proxies defined as 'an individual who uses a social media account for or supports the use of a social media account by another person'.